PALATABILITAS BAKSO DAN SOSIS SAPI ASAL DAGING SEGAR, DAGING BEKU DAN PRODUK KOMERSIAL - Yayu Zurriyati (State Islamic University of Sultan Syarif Kasim Riau, 2011)
Meatball and sausage are two types of popular meat processing. This research was aimed to determine and comparethe palatability of meatball and sausage from fresh beef meat, frozen beef meat and commercial product. The research methodwas level of preference /acceptance of panelists with the organoleptic test included color, aroma, texture, elasticity and flavorof meatball and sausage with five criteria of hedonic scale of: 1 (strongly dislike), 2 (not like), 3 (neutral), 4 (like) and 5 (verylike). The values from panelists were statistically analyzed by using a non parametric Kruskal-Wallis method. The resultshowed that the characteristics of color, aroma, texture, elasticity and taste of the meatball and sausage from fresh meat,frozen meat or commercial product did not differ, although the panelists tended to be more like the meatball and sausage fromfresh meat.